Radiolytic Hydrogen Production in the Subseafloor Basaltic Aquifer - Dzaugis, Mary E.; Spivack, Arthur J.; Dunlea, Ann G.; Murray, Richard W.; D’Hondt, Steven (Frontiers in Microbiology, 2016)
Hydrogen (H2) is produced in geological settings by dissociation of water due to radiation from radioactive decay of naturally occurring uranium (238U, 235U), thorium (232Th) and potassium (40K). To quantify the potential significance of radiolytic H2 as an electron donor for microbes within the South Pacific subseafloor basaltic aquifer, we use radionuclide concentrations of 43 basalt samples from IODP Expedition 329 to calculate radiolytic H2 production rates in basement fractures. The samples are from three sites with very different basement ages and a wide range of alteration types. U, Th and K concentrations vary by up to an order of magnitude from sample to sample at each site. Comparison of our samples to each other and to the results of previous studies of unaltered East Pacific Rise basalt suggests that significant variations in radionuclide concentrations are due to differences in initial (unaltered basalt) concentrations (which can vary between eruptive events) and post-emplacement alteration. In our samples, there is no clear relationship between alteration type and calculated radiolytic yields. Local maxima in U, Th, and K produce hotspots of H2 production, causing calculated radiolytic rates to differ by up to a factor of 80 from sample to sample. Fracture width also greatly influences H2 production, where microfractures are hotspots for radiolytic H2 production. For example, H2 production rates normalized to water volume are 190 times higher in 1 μm wide fractures than in fractures that are 10 cm wide. To assess the importance of water radiolysis for microbial communities in subseafloor basaltic aquifers, we compare electron transfer rates from radiolysis to rates from iron oxidation in subseafloor basalt. Radiolysis appears likely to be a more important electron donor source than iron oxidation in old (>10 Ma) basement basalt. Radiolytic H2 production in the volume of water adjacent to a square cm of the most radioactive SPG basalt may support as many as 1500 cells.